Normal reference ranges for the left ventricular mass and left ventricular mass index in preterm infants - Lulu Abushaban; Jebaraj Rathinasamy; Prem N Sharma; Mariappa Thinakar Vel (Wolters Kluwer Medknow Publications, 2020)
Objective :The objective of this study is to establish normal reference ranges for the left ventricular mass (LVM) and LVM index (LVMI) in preterm infants according to the body surface area (BSA) and assess their correlation with body weight and gestational age. Subjects and Methods :In a prospective study, 268 preterm babies who fulfilled the criteria for inclusion were examined. Echocardiograms were performed to measure the LVM and LVMI on 0-6 day (s) of life and at weekly intervals until the babies reached 36 weeks. The preterm infants were divided into six groups according to their BSA: 0.07-0.08 m2, 0.09-0.10 m2, 0.11-0.12 m2, 0.13-0.14 m2, 0.15-0.16 m2, and 0.17-0.19 m2. Results : The mean gestational age was 29.8 (±2.38 standard deviation [SD]) weeks, ranging from 24 to 35 weeks. The mean body weight was 1479 (±413 SD) g, ranging from 588 to 3380 g, and the mean BSA was 0.13 m2, ranging from 0.07 to 0.19 m2. The LVM correlated well with the gestational age, body weight, and BSA. The LVMI correlated well with body weight and BSA. Reference ranges with the mean ± SD, range, and interquartile range were calculated for the LVM and LVMI according to the BSA. A significant gradual increase was observed in a LVM with increasing BSA. Overall, a progressive and significant increase in the LVM was observed during the first 9 weeks of life. Conclusion :The LVM and LVMI exhibited a significant correlation with the BSA and body weight. This study provides reference data that can be used as a normal reference tool for the LVM and LVMI for preterm infants based on the BSA.